Computer Science and Its Applications 5th IFIP TC 5 International Conference, CIIA 2015, Saida, Algeria, May 20-21, 2015, Proceedings - Amine, Abdelmalek; Bellatreche, Ladjel; Elberrichi, Zakaria; Neuhold, Erich J.; Wrembel, Robert (IFIP Advances in Information and Communication Technology, 2015)
This book constitutes the refereed proceedings of the 5th IFIP TC 5 International Conference on Computer Science and Its Applications, CIIA 2015, held in Saida, Algeria, in May 2015. The 56 revised papers presented were carefully reviewed and selected from 225 submissions. The papers are organized in the following four research tracks: computational intelligence; security and network technology; information technology; and software engineering.